Book Review: Victoria Canning. Torture and torturous violence. Transcending the definitions of torture - Pérez-Sales, Pau (Torture Journal, 2023)
Book review by Pau Pérez-Sales on Victoria Canning's book "Torture and torturous violence. Transcending the definitions of torture"